Effect of Customer Satisfaction on Customer Loyalty and Marketing Organization Performance in B2B Market Over Heavy Equipment Company - Yora Harzaviona; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
In Indonesia's heavy equipment industry, there are still many sales and rental companies that still do not realize the importance of customer satisfaction to increase the retention and progress of their companies. This study aims to analyze the effect of customer satisfaction on customer loyalty and the performance of marketing organizations in the B2B market in Indonesia's heavy equipment industry. The goal is that massive equipment sellers and rentals know that increasing customer satisfaction can increase the long-term security of the company's future earnings. This quantitative research was conducted by distributing questionnaires to 38 massive equipment companies in Jakarta and Banten from February to April 2020. They are then testing the results using the SmartPLS 3.0 application. The results showed that the customer satisfaction variable has a positive effect on customer loyalty and negative on the marketing organization's performance. Meanwhile, customer loyalty has a positive and significant effect on the performance of the marketing organization.